Pulmonary nitric oxide in astronauts before and during long-term spaceflight - Karlsson, Lars L.; Gustafsson, Lars E.; Linnarsson, Dag (Frontiers in Physiology, 2024)
Introduction: During exploratory space flights astronauts risk exposure to toxic planetary dust. Exhaled nitric oxide partial pressure (PENO) is a simple method to monitor lung health by detecting airway inflammation after dust inhalation. The turnover of NO in the lungs is dependent on several factors which will be altered during planetary exploration such as gravity (G) and gas density. To investigate the impacts of these factors on normal PENO, we took measurements before and during a stay at the International Space Station, at both normal and reduced atmospheric pressures. We expected stable PENO levels during the preflight and inflight periods, with lower values inflight. With reduced pressure we expected no net changes of PENO.Material and methods: Ten astronauts were studied during the pre-flight (1G) and inflight (µG) periods at normal pressure (1.0 ata [atmospheres absolute]), with six of them also monitored at reduced (0.7 ata) pressure and gas density. The average observation period was from 191 days before launch until 105 days after launch. PENO was measured together with estimates of alveolar NO and the airway contribution to the exhaled NO flux.Results: The levels of PENO at 50 ml/s (PENO50) were not stable during the preflight and inflight periods respectively but decreased with time (P=0.0284) at a rate of 0.55 (0.24) (mean [SD]) mPa per 180 days throughout the observation period, so that there was a significant difference (P<0.01, N=10) between gravity conditions. Thus, PENO50 averaged 2.28 (0.70) mPa at 1 G and 1.65 (0.51) mPa during µG (-27 %). Reduced atmospheric pressure had no net impact on PENO50 but increased the airway contribution to exhaled NO. Discussion: The time courses of PENO50 suggest an initial airway inflammation, which gradually subsided. Our previous hypothesis of an increased uptake of NO to the blood by means of an expanded gas-blood interface in µG leading to decreased PENO50 is neither supported nor contradicted by the present findings. Baseline PENO50 values for lung health monitoring in astronauts should be obtained not only on ground but also during the relevant gravity conditions and before the possibility of inhaling toxic planetary dust.